A chromosome-level genome assembly of Cydia pomonella provides insights into chemical ecology and insecticide resistance - Fanghao Wan (Nature Portfolio, 2019)
The codling moth, Cydia pomonella, is one of the major pests of pome fruit (apples and pears) and walnuts. Here, the authors sequence and analyze its genome, providing insights on olfactory and detoxification processes that may underlie its worldwide expansion.